Development of microsatellite loci for Cryptocarya mandioccana Meisner (Lauraceae) and their genotyping success in different tissues - Carvalho, Thabata [UNESP]; Garcia, Giuliana [UNESP]; Carvalho, Carolina Silva [UNESP]; Palma-silva, Clarisse [UNESP]; Culot, Laurence [UNESP] (Instituto de Botânica, 2017)
Nine polymorphic microsatellite loci were isolated and characterized for Cryptocarya mandioccana Meisner, a tree from the Atlantic Rainforest with seeds dispersed by large animals. The loci were characterized using 48 individuals from two populations and their genotyping success tested in four tissues: leaves from adults and seedlings, and two diaspore maternal tissues. Maternity analyses were also performed on diaspores and leaves from nine adult trees. The number of alleles per locus ranged from nine to 15 and the observed and expected heterozygosities ranged from 0.214 to 0.864 and 0.745 to 0.892, respectively. The loci genotyping success did not significantly differ between tissues and varied from 56 to 96%. The microsatellites showed enough polymorphism to assign the nine adult trees to their diaspores. The successful genotyping in all tissues and identification of mother trees show that the microsatellites are suitable for studies such as spatial genetic structure and maternity analyses.

Nove locos de microssatélites polimórficos foram isolados e caracterizados para Cryptocarya mandioccana Meisner, uma árvore da Mata Atlântica cujas sementes são dispersas por grandes animais. Os locos foram caracterizados usando 48 indivíduos de duas populações e o sucesso de genotipagem testado em quatro tecidos: folhas de adultos e plântulas, e dois tecidos maternos de diásporos. Análises de maternidade foram também realizadas em diásporos e folhas de nove árvores adultas. O número de alelos por loco variou de nove a 15 e as heterozigosidades observada e esperada de 0,214 a 0,864 e 0,745 a 0,892, respectivamente. O sucesso de genotipagem dos locos não diferiu entre os tecidos e variou de 56 a 96%. Os microssatélites mostraram polimorfismo suficiente para atribuir as nove árvores aos seus diásporos. O sucesso de genotipagem em todos os tecidos e a identificação das árvores mães mostraram que os microssatélites são adequados para estudos como estrutura genética espacial e análise de maternidade.
Desenvolvimento de locos de microssatélites para Cryptocarya mandioccana Meisner (Lauraceae) e o sucesso de genotipagem em diferentes tecidos
Keywords: Atlantic forest; Lauraceae; maternity analysis; microsatellite; seed maternal tissue; análise de maternidade; Lauraceae; Mata Atlântica; microssatélite; tecido materno das sementes